Homes within reach : - Friedman, Avi (J. Wiley, 2005)
Homes Within Reach provides the first systematic guide for planning, designing, and constructing modest, yet high-quality, homes. From siting and foundations to systems, layouts, and interior and exterior finishes, it covers dozens of design and construction techniques that promote housing quality with sensitivity to lowering costs.